Learners’ impressions and pressures in the process of appropriation of Portuguese as a foreign language: proficiency and switching languages on a collision course - Cunha, Ary (2017)
Researches about linguistic and cultural heterogeneity in foreign language classes have been helping teachers to suit their teaching practices to the special features of plurilingual and pluricultural students. However, in the Portuguese Foreign Language (PFL) context, this phenomenon has been studied especially from a cultural point of view, leaving aside other equally important aspect of this heterogeneity: the linguistic. Our purpose here is to present the first results of an ethnographic research, focused on the plurilingual reality of a PFL class in the Federal University of Pará (UFPA). The data collected by interview (with students) and teaching actions observations were treated in a qualitative way comprising two moments of reflection: the first take is about contextual aspects and about the individuals; the second is focused on the ways that students deal with their repertoire bi(pluri)lingual, mainly concerning to their linguistic representations and their linguistics actions. On the one hand, the first analyzes show that code-switching is an unavoidable trait in bi(pluri)lingual classes (however, it is often seen as a secret practice that, if caught in the act, is reproached by teacher and discouraged by the classmates) and, on the other hand, an educational resource that, properly dealt, is likely to turn more effective the learning of a language (here, PFL). Hence it’s necessary to take into account the linguistic repertoires of these students, using this knowledge in an open and dynamic perspective, leading to the expansion students’ communicative competence in the target language.---DOI: http://dx.doi.org/10.22409/gragoata.2017n42a863